Design of Ordering System Using Web-Based Quick Response Code (Qr Code) Technology at Paolo Fest Cafe - Putri, Dinda Aisya; Kusmintarti, Anik; Jaswadi, Jaswadi (PT FORMOSA CENDEKIA GLOBAL, 2024)
The goal of this research is to develop an efficient business process model to resolve issues related to the ordering cycle of food and beverages at Paolo Fest Café. This study employs the Research and Development (R&D) approach and follows the ADDIE methodology, which includes three stages: analysis, design, and development. The research findings underscore the need for a website system that showcases the Paolo Fest Café menu, starting from selecting the table number to checking out. Payments can be conveniently made using the name or table number and can be processed either at the cashier or by customers requesting the bill at their table. This system eliminates the need for waiters to take orders individually and simplifies the payment process for customers. Furthermore, daily or monthly transaction reports can be easily generated using the website's transaction history feature, removing the necessity for manual recalculations.